PROSPECTS FOR INCREASING INVESTMENT EFFICIENCY BY PRODUCTION VOLUME AT INDUSTRIAL ENTERPRISES - Nosirov Khusanboy , Bakhodirjon ugly (THE INNOVATION ECONOMY, 2025)
This article examines the prospects for enhancing investment efficiency in Uzbekistan’s industrial enterprises through increased production volumes. The study analyzes the impact of production capacities, technological modernization, and financial resources. A mixed-methods approach was employed, combining qualitative analysis (of legislation and enterprise documents) and quantitative analysis (of statistical data for 2020 2024). Findings indicate that higher production volumes improve investment returns, but infrastructure constraints, skill shortages, and financial barriers persist. Recommendations tailored to Uzbekistan’s context are provided